Prediction of Life Expectancy in Indonesia by Implementing Website-Based Lagrange Polynomial Interpolation - Maarip, Syamsul; Hermansyah, Aam; Hadraeni, Sopi Nuryani; Miqdad, Salman; Nuryadin, Ardhan Dimas; Yuliyanti, Siti (Universitas Sanata Dharma, 2024)
Life Expectancy (AHH) is a measurement of the average human lifespan accepted and used to assess the quality of health and welfare of a country's population. Accepted to develop a prediction system that can be easily accessed by the general public via a web platform. The method used to predict is the Lagrange polynomial interpolation method. The Lagrange polynomial interpolation method was chosen because it can model irregular numerical data with a fairly high level of accuracy. The data used to predict AHH comes from the Indonesian Central Statistics Agency (BPS). Known data on life expectancy in Indonesia for men from 2020 to 2023 shows 69.59, 69.67, 69.93 and 70.17. Predictions for 2024, 2025 and 2026 respectively show 70.19, 69.79, 68.77 with a Root Mean Squared Error result of 0.085875 or around 8.58% of the total data tested. The results of implementing the Lagrange polynomial interpolation method into an application in the form of this website show that this method is able to provide accurate predictions for life expectancy in Indonesia and can make it easier to use.Keywords: Interpolasi, Polinom Langrange, Life Expectancy, prediction, lifespan